Software piracy in Singapore. - Gok, Joanna Yin Yin. (2008)
This study examines the relationship between existing legislation and the protection of computer software. A survey was implemented to discern the attitudes of members of the general public towards copyright issues and their perceptions on efforts by the Singapore Government to reduce the sale of pirated software and compact discs.